Poverty and Reaction to Crime – Irresponsibility Proven - Petrovec, Dragan; Tompa, Gašper; Šugman, Katja (Sociologija. Mintis ir veiksmas, 2007)
The article scrutinizes issues regarding the definition of wealth or poverty and reaction to crime as reflected by the number of prisoners in the development of West European countries as well as the development of the new member states, former countries in transition. Authors point out the problem of implementations of the principles of democracy, economic development not only in new member states, but rather globally. They stress that the traditional criterion for measuring wealth (GDP) is not sufficient to understand and evaluate different social phenomena, including crime and crime policy. For the more precise evaluation we need a so-called Human Poverty Index (HPI) which is a multidimensional measure of poverty. The HPI shows deprivation in four basic dimensions: health, education, material standards and social exclusion. Using this tool authors emphasize strong correlation between inequality and the number of prisoners in the transition countries, which leads to a conclusion that countries in transition when establishing democracy do not care much about the welfare state by introducing a safety net. The consequence is that a small part of the population became extremely rich, preventing, thus, democratic development of a political system. Authors criticize that in most cases transition countries blindly follow USA, instead of creating a welfare state. With this regard it should be stressed that widening the gap between rich and poor citizens in transition countries raise threat to democratic system turning into an oligarchy. Furthermore, it leads to the more tough approach towards crime and crime policy.
Keywords: poverty; crime; social policy; democracy